Instilling The Character of Mutual Cooperation Through a Pop-Up Book Project in Social Studies Classes - Raudatul Jannah; A. Fatikhul Amin Abdullah (Universtias Islam Negeri Madura, 2026)
Cooperation is an essential component of character education and one of the core dimensions of the Profil Pelajar Pancasila. However, in daily classroom practice among seventh-grade students at MTs Riyadul Ulum Bicorong, this value had not been fully reflected, as many students preferred to work individually and were not accustomed to collaborative learning. Through the implementation of a pop-up book project in Social Studies learning, noticeable positive changes emerged in students’ social behavior, including increased cooperation, empathy, and shared responsibility. This study aims to describe the process of cultivating collaborative character through the pop-up book project and to examine the condition of students’ cooperative character after participating in the activity. This research employed a qualitative case study design. Data were collected through interviews, observation, and documentation, validated through triangulation of sources and methods. The findings indicate that cooperative values developed naturally through group discussions, task distribution, and mutual assistance during the project and continued to appear in students’ daily learning activities. Thus, the pop-up book project proved effective in fostering cooperative character in Social Studies learning